Decoupled choice-driven and stimulus-related activity in parietal neurons may be misrepresented by choice probabilities - Adam Zaidel (Nature Portfolio, 2017)
Choice-related signals in neuronal activity may reflect bottom-up sensory processes, top-down decision-related influences, or a combination of the two. Here the authors report that choice-related activity in VIP neurons is not predictable from their stimulus tuning, and that dominant choice signals can bias the standard metric of choice preference (choice probability).